The physical and mental health of middle aged and older adults on the autism spectrum and the impact of intellectual disability - Bishop-Fitzpatrick, Lauren; Rubenstein, Eric (Research in autism spectrum disorders, 2019)
People on the autism spectrum may have more physical and mental health conditions in midlife and old age compared to the general population. This study describes the physical and mental health of a unique sample of all middle aged and older Wisconsin Medicaid beneficiaries with an autism spectrum disorder diagnosis and tests differences between those with and without co-occurring intellectual disability. Using de-identified Medicaid claims data for 143 adults with a recorded autism spectrum disorder diagnosis aged 40–88 years with any Wisconsin Medicaid claims in 2012 through 2015, we extracted diagnoses for physical and mental health conditions from fee-for-service claims. Logistic regression analyses—controlling for sex, race, and age—compared the adjusted odds of physical and mental health conditions for those with and without intellectual disability. Many physical and mental health conditions, including immune conditions (70.6%), cardiovascular disease (49.0%) and its risk factors (46.2%), sleep disorders (85.3%), gastrointestinal disorders (49.7%), neurologic conditions (55.9%), and psychiatric disorders (72.0%) were highly prevalent in our full sample. Although there were many similarities between those individuals with and without co-occurring intellectual disability, middle aged and older adults on the autism spectrum had higher prevalence of epilepsy and lower prevalence of depression and anxiety compared to those without co-occurring intellectual disability. Findings suggest that people on the autism spectrum have a high prevalence of physical and mental health conditions in midlife and old age, regardless of intellectual disability status.